2020
DOI: 10.4081/monaldi.2020.1322
|View full text |Cite
|
Sign up to set email alerts
|

First MDCT evidence of ruptured aberrant left subclavian artery aneurysm in right aortic arch, Kommerell’s diverticulum and extrapleural hematoma treated by emergency thoracic endovascular aortic repair

Abstract: Spontaneous ruptured aneurysm involving an aberrant subclavian artery with a right-sided aortic arch and Kommerell’s diverticulumis a rare life-threatening condition that can be treated successfully if promptly identified. Multidetector Computed Tomography angiography is the first line imaging modality of thoracic vascular anomalies diagnosis. We report the case of a 74-year-old man suffering from this emergency ondition with mediastinal hematoma mostly extending to the left-side extrapleural cavity. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, it does not solve the problem of the proximal landing zone and has been associated with complications such as branch occlusion, endoleaks, and stent-graft migration [31,33]. One of its main advantages is that it can be performed in one or two stages, depending on the patient's surgical risk and general clinical condition [20].…”
Section: Hybrid Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it does not solve the problem of the proximal landing zone and has been associated with complications such as branch occlusion, endoleaks, and stent-graft migration [31,33]. One of its main advantages is that it can be performed in one or two stages, depending on the patient's surgical risk and general clinical condition [20].…”
Section: Hybrid Approachmentioning
confidence: 99%
“…Sica et al [20] reported the case of a 74-year-old male patient with a saccular 70 mm Type II rKA associated with an anomalous course of the left brachiocephalic vein, which coursed posteriorly to the ascending aorta, and joined the right brachiocephalic vein to form the superior vena cava. Besides, a hematoma of the descending aorta was found, forming an extrapleural hematoma.…”
Section: Hybrid Approachmentioning
confidence: 99%
See 1 more Smart Citation